Soil biological activity in a Pinus laricio forest in Sila - Fioretto A.; Musacchio A.; Palermo A.M.; Papa S.; Pellegrino A. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
This work is a synthesis of studies performed in a Corsican pine forest in Sila Mountains (Calabria, South Italy) throughout six years and concerns soil respiration, soil microbial and fungal biomass, asymbiotic nitrogen fixation, N20 and CH4 emissions, denitrifying activity, litter decomposition and nutrient release. Microbial respiration of upper soil layer and decomposing pine needles showed patterns that matched the seasonal changes in moisture content. Asymbiotic N2 fixation (ARA) in litter and soil provide up to 1.6 kg N ha-1Y-1. Both litter and soil showed similar rates and patterns of ARA, denitrifying activity and trace gases emissions. Decomposition rate of Corsican pine litter, followed for 2.5 years was very low. By considering the nutrient dynamics during litter decomposition, the following ordered series of relative mobility: K>Mn>Mg>C>Ca>S>N>Zn>Cu
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)